Technology-Based Project-Based Learning in Teaching Content Subjects in University: A Study of Need Analysis - Untari, Fatimah Dwi; Ni Nyoman Padmadewi (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
Technology plays an important role in the 21st century. Technology-based project-based learning is needed by lecturers in teaching content courses and analyzing learning characteristics. Therefore this study aims to analyze the conceptual framework for implementing technology-based project-based learning needed in teaching content courses in tertiary institutions. The subjects of this study were several lecturers at the STKIP Agama Hindu Singaraja which included four lecturers who taught content courses. This study used a mixed methods approach paradigm with a mixed methods explanatory design, in which the qualitative research design was more dominant. The instrument used in the data collection process is a questionnaire for quantitative research. Whereas qualitative research uses interview guidelines in which the questions to be asked have been prepared and there is also an analysis of documents such as syllabus, semester lesson plans, and lecture contracts. In analyzing the data, the researcher also uses the OEM (Organizational Elements Model) and CIPP models which analyze data based on context, input, process, and product. Researchers analyze based on current conditions and expected conditions so that the needs of each lecturer are known when teaching content courses. The results of the research that has been collected are the lack of readiness between lecturers and students in implementing project-based learning in the classroom. Therefore, institutions need a conceptual framework regarding the implementation of technology-based project-based learning so that the content provided must be in accordance with 21st century skills where the focus of this learning is students.